Effect of palm peat as an alternative substrate for coconut peat on the morpho-physiological parameters of Cucumis sativus L. (Cucurbitaceae) - Azizi, Iraj; Asadi, Mohammad (Acta Biologica Szegediensis, 2025)
Soilless cultivation offers a viable alternative to soil-based methods for greenhouse crops. Palm peat has potential as an organic substrate in hydroponic systems, providing an alternative to conventional substrates like coconut peat. Cucumis sativus (cucumber) is a widely cultivated plant with significant nutritional value globally. This study evaluated the effects of two substrates—palm peat and coco peat—compared to soil (control) on the morphological and physiological characteristics of cucumber plants under greenhouse conditions in a completely randomized design. Key parameters, including plant height, number of lateral branches, leaf number and diameter, and fruit number and width were assessed at three intervals (15, 45, and 70 days). Additional parameters were measured on the 60th day. Analysis of variance (ANOVA) revealed significant differences in the physical and biochemical properties of the substrates, including EC, BD, pH, CEC, and WHC. Significant treatment effects were also observed on plant height, number of lateral branches, root fresh weight, leaf number and diameter, fruit number, width, and weight, as well as proline content. However, differences in relative water content (RWC), root dry weight, chlorophyll, and carotenoid content were not significant. This study highlights the positive influence of cultivation substrates on cucumber growth and development. Palm peat emerged as a promising cost-effective alternative to coco peat in soilless cultivation systems.